Workers’ Commuting Migration from District to City of Semarang by Rapid Transit Busses (Komunitas, 2016)
Migration phenomena, especially internal migrations which are usually called commuting migration, take place almost in the entire parts of Indonesia. One commuting migration phenomenon is shown by workers of Semarang District. The purpose of this study is to partially analyze the influence of income, education, marital status, land ownership, sex, and age variable upon workers’ commuting decision of Semarang District. This study uses both primary, obtained from questionnaires of 100 respondents, and secondary data. The results of binary logistic regression model analysis in this study show that two independent variables of income and education significantly influence workers’ commuting decision while marital status, land ownership, sex, and age variable do not influence workers’ commuting decision.